ANALISIS PENGEMBANGAN UMKM BERBASIS POTENSI LOKAL DI DESA PADANG PANJANG KECAMATAN ALOR TIMUR KABUPATEN ALOR - Sifra Eunike Lauring; Silpa Bilha Fanau; Petrus Mau Tellu Dony; Yermia S. Wabang (Adiba Aisha Amira, 2026)
This study aims to analyze the condition of Micro, Small, and Medium Enterprises (MSMEs) in Padang Panjang Village and to explore opportunities for developing MSMEs based on the village’s local potential. Data were obtained through interviews with village officials and community members as primary sources. The findings show that MSMEs in Padang Panjang Village are still relatively simple and limited to traditional weaving crafts, carpentry, and the trade of agricultural products. Nevertheless, the village possesses significant local potential, such as weaving skills, cultural traditions, strong social bonds within the community, and the tourism potential of the Padang Panjang Dam. These potentials provide promising opportunities for the development of creative economy–based MSMEs and local products. However, MSME development still faces several challenges, including limited capital, lack of market access, low managerial skills, and suboptimal training and business assistance. To address these issues, strategies for strengthening MSMEs are needed, such as human resource capacity building, forming MSME groups, product innovation training, utilizing digital technology for marketing, and enhancing collaboration between the community and village government. Active community participation in preserving and developing local crafts, along with village government support through coaching, financial facilitation, and institutional strengthening, are crucial factors in improving MSME competitiveness. Overall, this study emphasizes that developing MSMEs based on local potential has strong potential to become a key driver of the economy in Padang Panjang Village, provided it is supported by appropriate strategies and the involvement of all stakeholders.